2017
DOI: 10.1111/cid.12514
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiological, and gene expression analyses in smokers and non‐smokers, Part 2: RCT on the late healing phase of osseointegration

Abstract: During the early phase of osseointegration, non-smokers and smokers present a similar, high implant survival. In contrast, smokers present a greater MBL, particularly at machined implants. HIF-1α baseline expression in the recipient bone and IL-6 expression in PICF cells are important molecular determinants for MBL after 90 days. It is concluded that smoking has an early effect on osseointegration, which is dependent on the implant surface properties and the local host response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…Similar results were reported in a recent randomized controlled trial by Sayardoust et al . Authors of the present investigation support the results by Sayardoust et al . as implants placed in smokers and never smokers had rough surfaces.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results were reported in a recent randomized controlled trial by Sayardoust et al . Authors of the present investigation support the results by Sayardoust et al . as implants placed in smokers and never smokers had rough surfaces.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that implant surface characteristics (such as rough and oxidized surfaces) play a role in enhancing osseointegration and bone‐to‐implant contact by mechanically interlocking bone with the rough irregularities on implant surface . In addition, such implant surface modifications have been shown to modulate the molecular activities for reduced inflammation and/or enhanced bone formation in experimental in vivo models and also around implants in humans . A retrospective, clinical, radiographic case‐control study assessed implant survival and CBL at turned and oxidized implants in periodontitis‐susceptible never smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the present observations for the daily clinical work remains to be established in future studies. Nevertheless, recently the PICF molecular data obtained after 1‐28 days in the present study was complemented by molecular PICF data after 60 and 90 days in the same patient cohort . Clinical parameters and radiological assessment of marginal bone loss at 90 days, were correlated with the molecular data of both PICF and baseline bone prior to surgery.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, recently the PICF molecular data obtained after 1-28 days in the present study was complemented by molecular PICF data after 60 and 90 days in the same patient cohort. 39 Clinical parameters and radiological assessment of marginal bone loss at 90 days, were correlated with the molecular data of both PICF and baseline bone prior to surgery. Multivariate regression analysis revealed that some of the detected genes were predictors of marginal bone loss.…”
Section: Methodological Considerationsmentioning
confidence: 99%